STRENGTHENING THE ISLAMIC DIGITAL PAYMENT SYSTEM THROUGH SHARIA ELECTRONIC WALLET (E-WALLET) - Bella, Firsty Izzata; Efendi, Nadya Fira (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The objective of this research is to propose a strategy to strengthen the islamic digital wallet or electronic wallet (e-wallet) in Indonesia to compete with its conventional counterparts. Qualitative research methods with study literature were chosen to explore previous research that had been discussed on e-wallets particularly from the Islamic perspective both at global and national levels through reputable journals, reports, and other supportive documents. The results depicted that the Islamic e-wallet can be optimized through four points, namely promotion, education, collaboration, and trust but remained fulfilling sharia compliance so that the values of Islamic teachings are not vanished. Promotions in the form of cashback can be substituted for points to be converted into donations through the Islamic crowdfunding platform. Education can be improved through social media platforms. The way is by coordinating with Islamic public figures, collaboration with merchants and service providers. Finally increasing trust by safeguarding user data and funds.